Hand osteoarthritis and MRI: development and first validation step of the proposed Oslo Hand Osteoarthritis MRI score. Issue 6 (24th March 2011) - Haugen, Ida K; Lillegraven, Siri; Slatkowsky-Christensen, Barbara; Haavardsholm, Espen A; Sesseng, Sølve; Kvien, Tore K; van der Heijde, Désirée; Bøyesen, Pernille
Abstract : Objectives: MRI scoring systems for hand osteoarthritis (HOA) are currently not available. The present work proposes the Oslo HOA MRI (OHOA-MRI) score and examines the intrareader and inter-reader reliability. Methods: Relevant HOA features were included in the initial version of the OHOA-MRI score after literature review and informal group discussions. After a training session and two calibration exercises (with three readers), features with low reliability and/or low prevalence were excluded, and feature definitions/gradings were improved. In the reliability exercise 3 readers independently evaluated MRI scans of distal interphalangeal (DIP) and proximal interphalangeal (PIP) joints in 10 patients with HOA according to the final proposed score. The reading was repeated after 1 week. Intraclass correlation coefficients (ICCs), percentage exact agreement/percentage close agreement (PEA/PCA) and smallest detectable difference were calculated. Results: The final proposed OHOA-MRI score includes assessment of synovitis, flexor tenosynovitis, erosions, osteophytes (OPs), joint space narrowing (JSN) and bone marrow lesions (BMLs) on a 0–3 scale, and absence/presence of cysts, malalignment (frontal/sagittal plane), collateral ligaments (CLs) and BMLs at CL insertion sites. Inter-reader reliability was very good for synovitis, erosions, OPs, JSN, malalignment (frontal) and BMLs (ICCs ≥0.83, PCA ≥89%), and good for flexor tenosynovitis (ICC 0.64, PCA 80%) and CL presence (ICC 0.79, PEA 63%). Cysts, malalignment (sagittal) and BMLs at CL insertion sites showed high PEA (≥85%), but poor to moderate ICCs (0.00–0.59). Intrareader reliability was similar. The reliability was generally highest in PIP joints. Conclusions: The proposed OHOA-MRI score could reliably assess HOA features. However, further validation is needed.